Design and performance analysis of slot-based DGS-MIMO for sub-band allocation in 5G/6G networks - Priethamje Vithya K; Varalakshmi L M (Institute of Advanced Engineering and Science, 2026)
Wireless communication systems are quickly evolving to fulfil the increasing need for higher spectral efficiency, lower latency, and seamless connectivity. Although the conventional multiple-input multiple-output (MIMO) architecture improves reliability and throughput, it still faces high hardware complexity, spectral inefficiency, and interference issues in dense environments. Existing solutions, such as double-sided microstrip patch antennas or 8×8 MIMO arrays, yield moderate improvements but are not flexible enough for next-generation networks. To overcome these limitations, this paper puts forward a slot-based distributed generalized spatial modulation (DGS-MIMO) framework, which integrates dynamic antenna subset activation and adaptive sub-band allocation. In this way, the number of radio frequency (RF) chains is reduced, power consumption is lower, and spectral utilization is improved. Experimental validation shows excellent impedance matching (return loss up to -36.29 dB), high gain (6.98 dB), high radiation efficiency, and low signal reflection (voltage standing wave ratio (VSWR) as low as approximately 1.03). These results prove the robustness and efficiency of the proposed system in comparison with conventional designs. Besides the performance enhancement, the framework has great potential to be applied in real-world 5G/6G applications, especially in internet of things (IoT) deployments and vehicular communication scenarios where scalability, energy efficiency, and reliability are important.